Elongation factor P controls translation of the mgtA gene encoding a Mg2+ transporter during Salmonella infection. Issue 4 (27th June 2018) - Choi, Eunna; Nam, Daesil; Choi, Jeongjoon; Park, Shinae; Lee, Jung‐Shin; Lee, Eun‐Jin
Abstract: Ribosome often stalls on mRNA sequences harboring consecutive proline codons. Elongation factor P (EF‐P) is required for the stalled ribosome to continue translation and thus the absence of EF‐P affects translation of the associated open reading frame. Here we report that EF‐P controls translation of the mgtA gene encoding a Mg 2+ ‐transporting ATPase from the intracellualr pathogen Salmonella enterica serovar Typhimurium. EF‐P's effect on mgtA translation is dependent on the 550th and 551st proline codons in the coding region and thus substitution of those proline codons eliminates EF‐P‐mediated control of MgtA protein without affecting the Mg 2+ ‐transporting activity of the mgtA gene. The Pro550 and Pro551‐substituted mgtA gene promotes Salmonella 's intramacrophage survival and mouse virulence, suggesting that EF‐P‐mediated translational control of the mgtA gene is required for Salmonella pathogenesis. Abstract : Salmonella enterica serovar Typhimurium harbors the mgtA gene encoding a Mg 2+ transporter, which has two consecutive proline codons in the coding region. Because these proline codons require elongation factor P to be translated, Salmonella decreases MgtA production despite increasing mgtA transcripts when EF‐P is absent. Moreover, substitution of the proline codons that eliminates EF‐P‐mediated control promotes virulence, suggesting that EF‐P‐mediated mgtA control is required for Salmonella pathogenesis.